Breaking the Glass Ceiling for Indonesian Migrant Workers: Legal-Political and Maqasid al-Shariah Analysis of Protection Policies - Aji (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research addresses the significance of protecting migrant workers through the lens of legal politics and maqasid al-shariah. Migrant workers, particularly women, face various structural challenges that create a “glass ceiling,” limiting their access to rights and welfare. Addressing gaps in prior research that largely focus on regulatory frameworks, this study highlights the relevance of maqasid al-shariah as a holistic approach to labor migration policies. Through a normative qualitative analysis of Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers and secondary data sources, this study demonstrates that the PPMI Law aligns with maqasid al-shariah by addressing legal, social, and economic protections. These protections correspond to hifzh al-aql (preservation of intellect), hifzh an-nasl (preservation of family), and hifzh al-mal (preservation of wealth). The findings affirm the law’s dual objectives: securing workers' welfare and aligning national policies with Islamic jurisprudence. Theoretically, this research contributes to the integration of maqasid al-shariah and legal-political analysis, offering a nuanced perspective on migrant worker protection. Practically, it informs policy-makers on enhancing labor migration frameworks by aligning them with maqasid al-shariah. Future research should incorporate field data to evaluate the law's implementation and explore its comparative applicability across diverse sociopolitical contexts.